Slavoj Žižek: live theory - Butler, Rex 19XX- (Continuum, 2005)
Slavoj Zizek is undoubtedly one of the world's leading cultural critics. His witty, psychoanalytically-inspired analyses of contemporary society have almost single-handedly revived the notion of ideology. This book provides a snapshot of the Zizek system.
Keywords: Žižek, Slavoj; Zizek, Slavoj; Žižek, Slavoj -- 1949-; Philosophie